IMPROVING NOBLE ACTORS IN CHILDREN AGED 5-6 YEARS BY DISCUSSION OF MORAL DILEMMA AT PAUD KHAIRIN ISLAMIC SCHOOL - Nurhayati, Nurhayati; masganti, Masganti (Al Hikmah Indonesian Journal of Early Childhood Islamic Education, 2024)
Moral education is very important to instill from an early age because this influences the communication process with the environment in the family, peers, school and society. This research is useful for improving children's morals, such as discipline, politeness, honesty, responsibility, implementation, social relationships and cleanliness, through discussions of moral dilemmas at PAUD Khairin Islamic School which is located at Jalan Tuamang No. 85. This research uses classroom action research. (PTK) or CAR is held by teachers in the class (school) where they teach, through a focus on improving or improving learning mechanisms and practices. This research was conducted in Kindergarten B class aged 5-6 years with a total of 13 students. The results of this research were made in two cycles, which included planning, implementation, observation and reflection. Researchers also applied observation sheets to determine the improvement in children's morals and evaluate their level of success. In the pre-cycle, in terms of assessing students' moral character, the criteria are not yet developed and are starting to develop. In cycle II, the development criteria increased, students' moral values ​​increased. there was an increase such as through classical completeness of 83.3%. This proves that the increase in children's morals, such as discipline, politeness, honesty, responsibility, implementation, social relations and cleanliness, increases through discussions of moral dilemmas at PAUD Khairin Islamic School.